(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
This paper presents new empirical findings in the academically sparse area of low-skilled worker management. Despite their important presence in the labour-intensive sector, a limited amount of research and study has been done regarding low-skilled worker attitude. This empirical paper studied 400 low-skilled Myanmar immigrant workers in the Thai seafood-processing industry to find out the level of their attitude toward job satisfaction, organizational commitment, turnover intention, and job characteristic factors. Descriptive analysis, t-test, ANOVA, correlation, and regression analysis are used in this study. The results reveal a mixture of evidence supportive to that of past literatures and a surprisingly contradictory result in the area of turnover intention. Through this new empirical finding, entrepreneurs and society gain a better understanding of low-skilled workers and understand how to manage and motivate this unique group of employees more effectively and efficiently in the future.Â